A reinterpretation of the value attributes of agricultural land for the valuation of farms bought for lifestyle purposes - Reed, Lily Lozelle (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD(Agric) (Agriculture))--University of Stellenbosch, 2009.